Hubungan pengetahuan dan kepatuhan membaca label pangan dengan obesitas pada pegawai Di Kota Yogyakarta - Odillia Embun Wenniar Pramesti; Hildagardis Meliyani Erista Nai; Ruth Surya Wahyu Setyaning (UHAMKA PRESS, 2026)
The prevalence of obesity among Civil Servants in Yogyakarta has reached 32.0%. In general, obesity is influenced by four factors: life style or behavior, individual factors, social factors, and environmental factors. The purpose of this study was to assess the relationship between knowledge and compliance with food label reading and obesity among civil servants working in government offices at the Yogyakarta City Hall Complex. The study used a quantitative method with a cross-sectional design. The sample size of 117 people was selected using cluster random sampling. Knowledge of food labels and compliance with reading packaged food labels were collected through interviews using a questionnaire. Obesity was assessed using the Body Mass Index indicator using secondary data for employee weight and height data. Bivariate analysis using the Lambda test showed that there was no relationship between food label knowledge and obesity in Civil Servants (p=0.668). In addition, there was a relationship between compliance with reading food labels (p=0.0001), energy intake levels (p=0.001), and physical activity (p=0.048) with obesity in Civil Servants. There was no relationship between food label knowledge and obesity and there was a relationship between compliance with reading food labels and obesity in Civil Servants. Employees are advised to increase compliance with reading food labels and physical activity, as well as having a good level of energy intake as an effort to prevent obesity.